Assessing limitations in published camel feeding studies: implications for smart feeding practices in meat and milk production - Alkhtib, Ashraf; Samool, Ali; Muna, Muhanad; Tamiru, Metekia; Naeem, Muhammad; Onuoha, Chris Chinemere; Wamatu, Jane; Burton, Emily (Frontiers in Animal Science, 2024)
Rearing camels in intensive production systems started in the last 20 years. This led to a considerable change in camel feeding and nutrition including the use of new feeds (i.e. gains, agricultural by-products, supplements). Therefore, research was conducted to determine the effect of using these feeds in camel meat and milk production. The existing studies on camel feeding and nutrition are scattered and lack both an appraisal and comprehensive summary.This systematic review analyses the ability of published feeding and nutrition studies to guide researchers, extension workers, and farmers in formulating rations for smart feeding of camels. The Web of Science database was used to collect all published and peer-reviewed articles on the effects of feeding options on camel meat and milk production using the following Boolean: camel AND (milk OR growth OR meat). The first search yielded 2475 unique entries. Screening of the title shortlisted 278 relevant articles and the summary and full text assessment identified 41 relevant articles (27 fattening studies and 14 milk production studies) that were reviewed in depth. The experimental diets in only two studies (out of 41 studies) were formulated considering camel feeding standards. It is concluded that the published peer-reviewed literature in the field of camel nutrition is limited in both quantity and quality in informing the camel production sector to design rations for smart feeding for meat and milk production.